Tuning in C-nociceptors to reveal mechanisms in chronic neuropathic pain - Jonas, Robin; Schnakenberg, Mark; Carr, Richard; Schmelz, Martin; Rukwied, Roman (Annals of neurology, 2018)
Objective Develop and validate a low-intensity sinusoidal electrical stimulation paradigm to preferentially activate C-fibers in human skin. Methods Sinusoidal transcutaneous stimulation (4Hz) was assessed psychophysically in healthy volunteers (n = 14) and neuropathic pain patients (n = 9). Pursuing laser Doppler imaging and single nociceptor recordings in vivo in humans (microneurography) and pigs confirmed the activation of “silent” C-nociceptors. Synchronized C-fiber compound action potentials were evoked in isolated human nerve fascicles in vitro. Live cell imaging of L4 dorsal root ganglia in anesthetized mice verified the recruitment of small-diameter neurons during transcutaneous 4-Hz stimulation of the hindpaw (0.4mA). Results Transcutaneous sinusoidal current (0.05-0.4mA, 4Hz) activated “polymodal” C-fibers (50% at ∼0.03mA) and “silent” nociceptors (50% at ∼0.04mA), intensities substantially lower than that required with transcutaneous 1-ms rectangular pulses (“polymodal” ∼3mA, “silent” ∼50mA). The stimulation induced delayed burning (nonpulsating) pain and a pronounced axon-reflex erythema, both indicative of C-nociceptor activation. Pain ratings to repetitive stimulation (1 minute, 4Hz) adapted in healthy volunteers by Numeric Rating Scale (NRS) -3 and nonpainful skin sites of neuropathic pain patients by NRS -0.5, whereas pain even increased in painful neuropathic skin by approximately NRS +2. Interpretation Sinusoidal electrical stimulation at 4Hz enables preferential activation of C-nociceptors in pig and human skin that accommodates during ongoing (1-minute) stimulation. Absence of such accommodation in neuropathic pain patients suggest axonal hyperexcitability that could be predictive of alterations in peripheral nociceptor encoding and offer a potential therapeutic entry point for topical analgesic treatment. Ann Neurol 2018;83:945-957